Interaction Studies in Urea-Phenol and Urea-Resorcinol Eutectics - P. Singh, Vijendra; Mittal, S.G.; Prakash, Jai (Asian Journal of Chemistry, 2010)
The phase interaction studies of urea-phenol (U-P) and urearesorcinol (U-R) were carried out as a function of their per cent composition in their proportionately prepared solutions. With reference to time (t = 0), a thermo-constancy (ΔT = 0) condition of stabilizing interactions for a fixed composition of urea-phenol and urea-resorcinol solutions were observed, thermally constant temperature values determined from cooling statistics of U-P and U-R solutions were plotted against their individual per cent compositions. From these phase diagrams eutectically thermodynamic values were derived and the results were explained in terms of eutectic coordinates.